(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Agrosilvopastoral practices are recognized as a link between agriculture, forestry and a sustainable strategy for land management, particularly in tropical and subtropical developing nations. This study examined the limitations of agrosilvopastoral practices among households in Ogun State. A well thought out questionnaire was used to gather information from 240 respondents in total. Descriptive statistics were used to analyze the data collected. Findings revealed that agrosilvopastoral practices were dominated by men, with a mean age and family size of 54 years and 6 persons respectively. More over half (62.25%) of the farmers were literate with mean years of experience in farming being 26years. Result revealed that inadequate capital (1st) is the most serious challenge facing the agrosilvopastoral households, followed by insect infestation (2nd), instability in market price (3rd), inadequate access to land for farming (4th), high cost of transportation (5th), insufficient market centers (6th), source of inputs (7th), technical knowledge (8th), mode of land acquisition (9th) and animal destruction of crops (10th). The study thereby recommends that extension workers from different organizations should educate farmers about agrosilvopastoral practices through seminars, and backing being offered to farmers in the terms of loans, hybrid seeds and credit provision for increased production.